Materi Sejarah Masa Hindu-Buddha dan Penggunaan Sumber Belajar Sejarah dalam Pembelajarannya di SMK - Nofiyah Mardiani; Umasih Umasih; Murni Winarsih (IAIN Syekh Nurjati Cirebon, 2019)
ABSTRACTLearning in Vocational Schools is learning aimed at improving intelligence, knowledge, personality, noble character, and the skills of students to live independently and to take further education in accordance with their vocational programs. learning resources used in vocational schools are expected to be very varied for this independence. learning resources can be physical and non physical. Types of learning resources include, messages (in the form of learning materials, folklore, fairy tales, advice, Islamic saga, story stories), people (learners), materials (transparency, films, slides, book tapes, pictures), equipment (ohp , tv, camera, blackboard), methods (lectures, discussions, simulations, independent learning), environment (rooms, studios, halls, prayer rooms, mosques). In history learning, these learning resources can be used. During the Hindu-Buddhist development, historical learning could use heritage buildings. Looking at the latest curriculum, that learning activities should force the student center to create creativity in learning. This study used qualitative methods for three schools using interview instruments to Indonesian history teachers and students as samples and documented studies about learning activities. The results found that the lack of creativity for teachers to utilize technology, especially the internet, one of which is to use films, documentaries or videos, and visit local cultural heritage sites and museums as media and sources of historical learning. So that it causes history learning to be delivered monotonously. The purpose of this study looks at the use of historical learning resources in Vocational Schools and the impact of the use of these learning resources. Until finally the purpose of this study is to provide solutions for ways of innovation and creation in history learning in vocational schools so that they are in accordance with their vocational training.Keywords: Keywords: Vocational High School (SMK), historical learning resources, history learning material on Hindu-Buddhist and Islamic development